Identification of genes involved in rice seed priming in the early imbibition stage. (1st March 2016) - Cheng, J.; Wang, L.; Zeng, P.; He, Y.; Zhou, R.; Zhang, H.; Wang, Z.
Abstract: Phase II of seed imbibition is a critical process during seed priming. To identify genes involved in rice seed priming, the altered proteins between the dry and imbibed (24 h) seeds were compared using a two‐dimensional gel electrophoresis system in this study. Ten significantly changed proteins (fold change ≥ twofold; P  <   0.01) were successfully identified, which could be categorised as carbohydrate and protein biosynthesis and metabolism‐related, signalling‐related, storage and stress‐related proteins. A meta‐analysis indicated that the highest expression of the identified genes was at the milk and dough stages and in the endosperm tissue. Quantitative real‐time PCR analysis showed that there was significant variation in gene expression (except FAD‐dependent oxidoreductase) in embryos during seed priming (0–48 h). The expression of genes associated with stress appeared at the early imbibition stage, while those associated with carbohydrate metabolism, protein synthesis and signalling increased at the late imbibition stage. Three identified proteins (glucose‐1‐phosphate adenylyltransferase large subunit, aminotransferase and prolamin precursor) had similar transcript and protein expression patterns in embryos. Based on phenotype and gene expression, the optimal stop time for seed priming is 24 h, when these three genes have relatively low expression, followed by significant induction during imbibition in embryos. These three genes are ideal candidate biomarkers for rice seed priming.